Perfil epidemiológico das pessoas submetidas à esofagectomia para câncer de esôfago no Hospital Universitário de Santa Maria entre 2008 e 2012 - Marasca, Felipe André (2014)
Esophageal cancer (EC) is among the ten most prevalent cancer in the world population and it presents a high-lethality rate. The Brazilian state of Rio Grande do Sul (RS) has the greatest estimate of new cases of esophageal cancer. The treatment is surgical in most cases.Studies regarding the hospital care of these patients are rare and may contribute to the planning of services and improvement of the attention given to these people. This work is characterized by a cross-sectional, descriptive and retrograde study using secondary data in order to obtain the epidemiological profile of patients diagnosed with EC who underwentesophagectomy at the University Hospital of Santa Maria (HUSM) between 2008 and 2012. The HUSM is a tertiary level hospital and is a reference in the central region of the state. It is considered an important hospital regarding surgeries of esophagus (more than 20 surgeries/year). The HUSM did not have a structured epidemiological profile of these patients. A number of 123 esophagectomies were performed in the period studied, being that 98 patients were men and 25 women. Among the patients, 45 were from Santa Maria and 78 from other cities. The annual distribution of the surgeries was homogeneous during the period studied. The most performed surgery was trans-hiatal without thoracotomy, of which were 77 cases. The most frequent histological type was Epidermoid Carcinoma, which presented 108 cases. The height of the most frequent injury was the middle third with 78 cases, followed by the inferior third with 40 cases. Sixteen deaths (13%) were registered.Regarding patients who were discharged from the hospital, 98% received oral diet. The level of preoperative albumin was more than 3.5 in 61 cases. The most common complications were respiratory. Cervical fistula occurred in 24 cases (19.5%). The waiting time between hospitalization and surgery showed that one patient waited just one day, and the maximum time was 55 days, with an average of 9.4 days (SD 7.8). The time between surgery and hospital discharge revealed that only one patient remained hospitalized for two days, who ended up passing away. The maximum hospitalization time was 129 days with an average of 17.6 days (SD 14.7). The time from hospitalization until discharge showed that the minimum time was eight days and the maximum time was 144 days with an average of 27 days (SD 16.6). Most patients (75%) stayed hospitalized forup to 32 days. This research may contribute to learn about the service